MMP9: A novel function in synaptic plasticity - Dziembowska, Magdalena; Wlodarczyk, Jakub (The international journal of biochemistry & cell biology, 2012)
► MMP-9 mRNA is locally translated in neurons and released in response to enhanced synaptic activity. ► MMP-9 is present at the dendritic spines bearing asymmetric synapses. ► MMP-9 influences dendritic spine morphology and plays a key role in synaptic plasticity associated with learning and memory. Matrix metalloproteinase-9 (MMP-9), an extracellularly acting, Zn2+-dependent endopeptidase is a subject to complex regulation at the level of transcription, mRNA dendritic translocation, and local translation as well as protein activation, as it is released extracellularly in a latent, pro-form with the enzymatic site covered by a propeptide that has to be cleaved off to reveal the activity. In neurons, MMP-9 is present at the postsynaptic domains of excitatory synapses. Here, we review the role of MMP-9 in induction of structural dendritic spine modifications and in synaptic plasticity. In particular, we focus on local translation, activity-dependent secretion and activation of MMP-9 leading to its role in long term potentiation and regulation of remodeling of dendritic spines.